Hello,
Solve x^4-x-2=0
According to Wolfram Alpha, the answer is
x=-1
x=\(\displaystyle \dfrac{1}{6}\, \left(\, 2\, -\, 4\, \sqrt[3]{\strut \dfrac{2}{47\, +\, 3\sqrt{249\,}}\,}\, +\, 2^{\frac{2}{3}}\, \sqrt[3]{\strut 47\, +\, 3\sqrt{249\,}\,}\, \right)\)
\(\displaystyle x\, \approx\, -0.17660\, \pm\, 1.20282i\)
But could anyone show me step by step how to solve this problem?
Solve x^4-x-2=0
According to Wolfram Alpha, the answer is
x=-1
x=\(\displaystyle \dfrac{1}{6}\, \left(\, 2\, -\, 4\, \sqrt[3]{\strut \dfrac{2}{47\, +\, 3\sqrt{249\,}}\,}\, +\, 2^{\frac{2}{3}}\, \sqrt[3]{\strut 47\, +\, 3\sqrt{249\,}\,}\, \right)\)
\(\displaystyle x\, \approx\, -0.17660\, \pm\, 1.20282i\)
But could anyone show me step by step how to solve this problem?
Last edited by a moderator: